Inflammatory pseudotumor mimicking primary hepatic malignant tumor with hepatitis B virus-related cirrhosis: A case report - KE, QINGHONG (D.A. Spandidos, 2013)
Inflammatory pseudotumors (IPT) of the liver are fairly uncommon lesions. IPTs are difficult to diagnose due to the absence of specific symptoms. The correct diagnosis is easily missed, particularly in livers with hepatitis B virus (HBV)-related cirrhosis. The current study presents the case of a 58-year-old male with a ten-year history of HBV infection, who was diagnosed with a primary liver tumor by computed tomography (CT) and magnetic resonance imaging (MRI). The α-fetoprotein levels ranged within normal limits. A local resection was performed and the histopathological analysis identified IPT of the liver. The patient recovered well following surgery.